2020
DOI: 10.1177/1098300719890065
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Positive Behavior Support Within Preschool Settings: Group Functional Assessment and CW-FIT

Abstract: Preschool is an important educational setting for child development, and problem behavior is a prevalent barrier within this setting. Preschool teachers have expressed the need for evidence-based classroom management interventions to address problem behavior. Class-Wide Function-Related Intervention Teams (CW-FIT) is an intervention that incorporates social skills training, group contingencies, and reinforcement to address problem behavior within classrooms. This intervention has been found to be socially vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
(57 reference statements)
0
12
0
2
Order By: Relevance
“…The social and psychological dimensions have an impact on academic learning, reading, mathematical skills, and healthy development (Burchinal et al, 2016;Palmer et al, 2018;Froiland, 2020). Psychosocial support is also connected to the school setting in terms of improving behavior and preventing behavioral problems and dysfunctions of the child (Bierman et al, 2013;Mahon et al, 2020). Psychosocial support toward children with particular difficulties such as trauma, divorce, or child abuse is emphasized (Kolltveit et al, 2012;Bretherton et al, 2013;Bullock et al, 2019).…”
Section: The Contexts Of Palestine and Norwaymentioning
confidence: 99%
“…The social and psychological dimensions have an impact on academic learning, reading, mathematical skills, and healthy development (Burchinal et al, 2016;Palmer et al, 2018;Froiland, 2020). Psychosocial support is also connected to the school setting in terms of improving behavior and preventing behavioral problems and dysfunctions of the child (Bierman et al, 2013;Mahon et al, 2020). Psychosocial support toward children with particular difficulties such as trauma, divorce, or child abuse is emphasized (Kolltveit et al, 2012;Bretherton et al, 2013;Bullock et al, 2019).…”
Section: The Contexts Of Palestine and Norwaymentioning
confidence: 99%
“…The social and psychological dimensions have an impact on academic learning, reading, mathematical skills, and healthy development (Burchinal et al, 2016 ; Palmer et al, 2018 ; Froiland, 2020 ). Psychosocial support is also connected to the school setting in terms of improving behavior and preventing behavioral problems and dysfunctions of the child (Bierman et al, 2013 ; Mahon et al, 2020 ). Psychosocial support toward children with particular difficulties such as trauma, divorce, or child abuse is emphasized (Kolltveit et al, 2012 ; Bretherton et al, 2013 ; Bullock et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additional dependent variables for Jolstead et al (2017) included rates of praise and reprimand states issued by preschool teachers. Similarly, Mahon et al (2020) also looked at the frequency of social skills (e.g., appropriately getting the teacher's attention) and problem behaviors (e.g., shouting, running in the classroom, noncompliance). Results showed that the CW-FIT intervention reliably increased on-task student behavior across all preschool classrooms in Jolstead et al, (2017) and Mahon et al (2020).…”
mentioning
confidence: 99%
“…Similarly, Mahon et al (2020) also looked at the frequency of social skills (e.g., appropriately getting the teacher's attention) and problem behaviors (e.g., shouting, running in the classroom, noncompliance). Results showed that the CW-FIT intervention reliably increased on-task student behavior across all preschool classrooms in Jolstead et al, (2017) and Mahon et al (2020). The CW-FIT intervention also increased teacher praise statements and decreased teacher reprimands in Jolstead et al (2017), as well as increased social skills and decrease problem behavior in Mahon et al (2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation